Keterbukaan Diri dan Regulasi Emosi Peserta didik SMP Korban Bullying - Ani Wardah (ILIN Institute Makassar, 2020)
This research aims to find out the description of Self-Disclosure and Emotion Regulation of Bullying victims in Junior High School Banjarmasin. This research used qualitative approach with descriptive qualitative design. The subjects are five junior high school students whom become the bullying victims with range of age between 13 – 15 years old. Technique of data collection used observation, interview, and documentation. Technique of data analysis used data reduction, data presentation, conclusion and verification. Validity test used in this research were credibility and verification test. The result of this research showed that Self-Disclosure and Emotion Regulation of Bullying victims in Junior High School 4 were in closed tendency. Emotion regulation of bullying victims consists of: strategies to emotion regulation is a person faith to handle a problem such like stay silent, crying, grumbling, and angry to the bullies. Engaging in goal directed behavior are a person ability to unaffected to negative emotion felt, do not run from the bullying victims problem and choose to focus in study and school. Control emotional responses is a person ability to control the emotion such like stay silent and calming down himself by be alone, punch back and mock the bullies. Acceptance of emotional response is a person ability to accept an event caused negative emotion by showing that bullying victims are capable to limit the impacts of bullying, therefore it will not reach too far their life. They considered as regular thing, not ashamed, surrender, and shy.